The Study of Host Immune Responses Elicited by the Model Murine Hookworms Nippostrongylus brasiliensis and Heligmosomoides polygyrus. Issue 4 (20th December 2017) - Bouchery, T.; Volpe, B.; Shah, K.; Lebon, L.; Filbey, K.; LeGros, G.; Harris, N.
Abstract: Hookworm infections ( Necator americanus or Ancylostoma duodenale ) represent a major neglected tropical disease, affecting approximately 700 million people worldwide, and can cause severe morbidity due to the need for these worms to feed on host blood. N. brasiliensis and H. polygrus, both rodent parasites, are the two most commonly employed laboratory models of experimental hookworm infection. Both parasites evoke type 2 immune responses, and their use has been instrumental in generating fundamental insight into the molecular mechanisms of type‐2 immunity and for understanding how the immune response can control parasite numbers. Here we provide a complete set of methods by which to investigate the natural progression of infection and the host immunological responses in the lung and intestine of H. polygyrus – and N. brasiliensis –infected mice. Detailed information is included about the most important parasitological and immunological measurements to perform at each time point. © 2017 by John Wiley & Sons, Inc.